Occupational exposures and genetic susceptibility to lung cancer and pleural mesothelioma: a systematic review - Sonja Milovanovic; Jovana Stojanovic; Roberta Pastorino; Ivo Iavicoli; Stefania Boccia (Epidemiology, Biostatistics and Public Health)
Background